The Role of Human Resource Development in Improving Employee Performance at PT. Ray Developer - Ray, Qonita; Fauzan Azhmy, Muhammad; Saskia, Saskia (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
This study explores the role of human resource development in enhancing employee performance at PT Ray Developer. Human resource development (HRD) is a crucial factor in improving employee productivity and effectiveness and achieving organizational goals. The research employs a qualitative approach with a survey method involving employees of PT Ray Developer as respondents. Data collection methods include a questionnaire designed to measure various aspects of HRD, such as training, career development programs, and performance evaluation, and their impact on employee performance. Data analysis indicates that the HRD programs implemented at PT Ray Developer significantly improve employee performance. Relevant training and structured career development programs have enhanced employee motivation, skills, and competencies, improving work outcomes and efficiency. The findings provide insights into investing in HRD to boost organizational performance. Recommendations include refining training programs to be more specific and developing more apparent career paths to support sustainable employee growth. This research also contributes to understanding the relationship between HRD and employee performance, offering guidance for other companies in designing effective HRD strategies.